Chế tạo và khảo sát tính chất của vật liệu compozit PVC/hỗn hợp than đen và tro bay biến tính - Toàn, Nguyễn Duy; Thanh Vân, Trần Thị; Thẩm, Đỗ Quang; Giang, Nguyễn Vũ; Chinh, Nguyễn Thúy; Hoàng, Thái (Vietnam Journal of Chemistry, 2017)
In this paper, fly ash was modified by stearic acid and mixed with carbon black N330 (CB) in order to prepare PVC/MFA/CB composites (total amount of MFA and CB is 10 wt% in comparison with PVC weight). The effect of CB loading on the morphology, melt viscosity, mechanical and electrical properties of PVC/MFA/CB composites were studied. It was found that CB improved processing ability, tensile strength, and elongation at break of the PVC/MFA composites. If the ratio of CB/MFA in the PVC/MFA/CB composites is 50/50, the torque of PVC/MFA/CB composites decreased 16 % and elongation at break increased 11 %. Dielectric loss was decrease meanwhile dielectric constant, AC resistivity and breakdown voltage (dielectric strength) of the PVC/MFA/CB composites were increase as raising CB content. Keywords. Polyvinylchlorua, PVC composite, carbon black N330, fly ash, dielectric constant, melt viscosity.